ANALISIS LINGKUNGAN GLOBAL DALAM PERSAINGAN BISNIS INTERNASIONAL - Priangani, Ade (JURNAL KEBANGSAAN, 2012)
The development of business environment in the millennium now indicated by the presence of business globalization and international competition, the more critical consumer demands for products with high quality, and waiting times are short, tight business competition, increasing technological capabilities, and decrease product life cycle. In short, companies are faced in the development of business environment driven by technology (technology-driven business). If the economy of the past (past economies), the economy is highly dependent on resources such as land, natural resources, equipment, and capital to create value, then the economy of the millennium, the economy depends heavily on the knowledge that has more value than physical assets for the organization. Human resources (HR) is involved in every activity, the company will be doing less physical work and the more do the job by using the capital of the brain, which we are familiar with intellectual capital.